Mal de Debarquement Syndrome: A Retrospective Online Questionnaire on the Influences of Gonadal Hormones in Relation to Onset and Symptom Fluctuation - Mucci, Viviana; Canceri, Josephine M.; Brown, Rachael; Dai, Mingjia; Yakushin, Sergei B.; Watson, Shaun; Van Ombergen, Angelique; Jacquemyn, Yves; Fahey, Paul; Van de Heyning, Paul H.; Wuyts, Floris; Browne, Cherylea J. (Frontiers in Neurology, 2018)
Introduction: Mal de Debarquement Syndrome (MdDS) is a condition characterized by a persistent perception of self-motion, in most cases triggered from exposure to passive motion (e.g. boat travel, a car ride, flights). Patients whose onset was triggered in this way are categorized as Motion-Triggered (MT) subtype or onset group. However, the same syndrome can occur spontaneously or after non-motion events, such as childbirth, high stress, surgery, etc. Patients who were triggered in this way are categorized as being of the Spontaneous/Other (SO) subtype or onset group. The underlying pathophysiology of MdDS is unknown and there has been some speculation that the two onset groups are separate entities. However, despite the differences in onset between the subtypes, symptoms are parallel and a significant female predominance has been shown. To date, the role of gonadal hormones in MdDS pathophysiology has not been investigated. This study aimed to evaluate the hormonal profile of MdDS patients, the presence of hormonal conditions, the influence of hormones on symptomatology and to assess possible hormonal differences between onset groups. In addition, the prevalence of migraine and motion sickness and their relation to MdDS were assessed. Method: Retrospective online surveys were performed in 370 MdDS patients from both onset groups. Data was analyzed using Fisher’s exact test or Fisher-Freeman-Hanlon exact test. When possible, data was compared with normative statistical data from the wider literature. Results: From the data collected, it was evident that naturally cycling female respondents from the MT group were significantly more likely to report an aggravation of MdDS symptoms during menses and mid-cycle (p<0.001). A few preliminary differences between the onset groups were highlighted such as in regular menstrual cycling (p=0.028), reporting menses during onset (p<0.016), and migraine susceptibility after onset (p=0.044). Conclusion: These results demonstrate a potential relation between hormone fluctuations and symptom aggravation in the MT group. This study is an important first step to suggest a hormonal involvement in the pathophysiology of MdDS and provides a base for further hormonal investigation. Future prospective studies should expand upon these results and explore the implications for treatment.